Cerpen Al-Barman dalam Antologi Cerpen Khammaratul Qittil Aswad Karya Najib Mahfuz: Analisis Struktural Model Farhud / Short Story Al-Barman in The Anthologi of Khammaratul Qittil Aswad by Najib Mahfuz: Structural Analysis Farhud’s Models - Hidayatun Ulfa; Reza Maulana Alfitra; Ibadurrohman Ibadurrohman (Jurusan Bahasa dan Sastra Arab Universitas Islam Negeri Alauddin Makassar, 2021)
يبحث هذا البحث عن قصة البرمان القصيرة فى ديوان خمارة القط الأسود الذي الفه نجيب محفوظ: تحليل فرهود البنائي. وهدف هذا البحث إلى وصف العناصر الداخلية فى قصة البرمان القصيرة التي ألفها نجيب محفوظ وإلى معرفة العلاقة بين تلك العناصر. وتحليل هذه القصة بتحليل فرهود البنائي. وتتكون العناصر الداخلية في القصة من الحكاية، والشخصية، والحبكة، والزمان والمكان، والفكرة. وبعد تحليل هذه القصة التي ألفها نجيب محفوظ يمكن الاستنتاج بأن هذه القصة تصف مشاكل حياة الموظف الحكومي في مصر الذي كان مليئا بالإجهاد العقلي. وكان هذا بسبب الشعور بعدم الرضا عن حياته.الكلمات المفتاحية: قصة البرمان القصيرة؛ ديوان خمارة القط الأسود؛ نجيب محفوظ؛ تحليل فرهود البنائيAbstract:This research discussed the short story Al-Barman in the anthology of Khammaratul Qittil Aswad by Najib Mahfuz: A Structural Analysis of Farhud’s Models. This research aimed to find the intrinsic aspects in the short story of Al-Barman by Najib Mahfuz and the relationships between the intrinsic aspects. This research applied Farhud’s structural analysis model. The intrinsic aspects included Al-hikayah (story), asy-syakhsiyyah (characterization), al-habkah (plot), Az-zaman wal-maka>n (the setting of time and place), al-fikrah (ideas). Having analyzed that short story, the researchers concluded that this short story was about the life problems of a civil servant in Egypt, which are filled with mental stress due to the sense of dissatisfaction with his life.